2011
DOI: 10.1111/j.1365-313x.2011.04851.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the large genome in Capsicum annuum occurred through accumulation of single‐type long terminal repeat retrotransposons and their derivatives

Abstract: SUMMARYAlthough plant genome sizes are extremely diverse, the mechanism underlying the expansion of huge genomes that did not experience whole-genome duplication has not been elucidated. The pepper, Capsicum annuum, is an excellent model for studies of genome expansion due to its large genome size (2700 Mb) and the absence of whole genome duplication. As most of the pepper genome structure has been identified as constitutive heterochromatin, we investigated the evolution of this region in detail. Our findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 46 publications
0
32
1
1
Order By: Relevance
“…Complex patterns of nested insertions of LTR-RTs have also been found in intergenic regions of other plant species with large genomes (SanMiguel et al, 1996;Wicker et al, 2001;Wicker et al, 2005;Park et al, 2012b). In this study, the two BACs containing no functional gene structure, BACs 8D23 and 6J17, are likely to be representative of intergenic or heterochromatic regions in the ginseng genome.…”
Section: Genome Size Expansion and Ltr-rts In Ginsengmentioning
confidence: 98%
See 2 more Smart Citations
“…Complex patterns of nested insertions of LTR-RTs have also been found in intergenic regions of other plant species with large genomes (SanMiguel et al, 1996;Wicker et al, 2001;Wicker et al, 2005;Park et al, 2012b). In this study, the two BACs containing no functional gene structure, BACs 8D23 and 6J17, are likely to be representative of intergenic or heterochromatic regions in the ginseng genome.…”
Section: Genome Size Expansion and Ltr-rts In Ginsengmentioning
confidence: 98%
“…(Suoniemi et al, 1996;Vicient et al, 1999), wheat (Charles et al, 2008;Salina et al, 2011) and pepper (Park et al, 2011(Park et al, , 2012b, have reported that the genomes expanded and were rearranged by accumulation of LTR-RTs. Our results suggest that LTR-RTs are also the main players in the enlargement and evolution of the ginseng genome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). The results suggest that LTR-RTs might play a major role in the increase of the genome size such as many other plants with large genomes size (SanMiguel et al 1996;Park et al 2012b).…”
Section: Overview Of a Ginseng Genome Structurementioning
confidence: 94%
“…LTR amplification technique displays is also efficient in examine genome structure and evolution in Solanaceous crop species, and in chromosome structure and transmission (Manetti et al, 2007(Manetti et al, , 2009Novakova et al, 2009;Park et al, 2012;Michael, 2014;Na et al, 2014;Tang et al, 2014).…”
Section: Retrotransposon-based Marker Systemsmentioning
confidence: 99%